Identifikasi faktor yang berhubungan dengan pemilihan alat kontrasepsi pada pasangan usia subur di Desa Sei Kamah I - Br Sirait, Frida Novira; Sanusi, Sri Rahayu; Arde M, Lanova Dwi (TROPHICO, 2023)
A country with a large population will have a high population density. Indonesia is now handling this problem. Based on information collected from the Sei Dadap District Family Planning Counseling Office from 583 couples of reproductive age in Desa Sei Kamah I in 2021, as many as 253 (43.30%) were actively registered as family planning participants. This study aimed to identify, analyze and explain the factors related to the selection of contraceptives for reproductive age couples (RAC) in Desa Sei Kamah I, Sei Dadap District, Asahan Regency. This research is an analytical survey research with a cross-sectional research design. The fixation of sample size in this study was calculated using the sample calculation formula, it calls the cross-sectional formula and obtained a sample of 82 respondents. This study has six independent variables, specifically: variables of age, number of children, level of education, level of knowledge, partner support, and pregnancy plans with the dependent variable being the choice of contraception at RAC. Data were collected by interview using a questionnaire and then analyzed using the chi-square test with a value of Î± = 0.05. The results showed that the variable related to the choice of contraceptives in RAC was the couple’s support (p=0.001). The cadres are expected to grow the husband’s support for their wife to use long-term contraceptives and bring awareness for the husband to participate in using long-term contraceptives, Man Operation Method (MOM) with involvement from public figures, because the husband’s support significantly affects the contraception that the respondent will choose.